2021
DOI: 10.1111/csp2.397
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of detection canines for avian botulism surveillance and mitigation

Abstract: Hawai'i's endangered waterbirds have experienced epizootics caused by ingestion of prey that accumulated a botulinum neurotoxin produced by the anaerobic bacterium Clostridium botulinum (avian botulism; Type C). Waterbird carcasses, necrophagous flies, and their larvae initiate and spread avian botulism, a food-borne paralytic disease lethal to waterbirds. Each new carcass has potential to develop toxin-accumulating necrophagous vectors amplifying outbreaks and killing hundreds of endangered waterbirds. Early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Searching for bird species through scat, carcasses, or eggs has resulted in sensitivity rates between 62.6% and 100% with precision reported between 50% to 100% (Arnesen et al, 2020;Bolton et al, 2021;Fukuhara et al, 2022;Reynolds et al, 2021). However, the study by Arnesen et al (2020), where dogs searched for rock ptarmigan (Lagopus muta) scat in lab conditions, had three dogs out of four perform no better than chance and none of the dogs or handlers had any previous experience of training for CDD work.…”
Section: Effi C Ac Y R Ate S Across Conte X Tsmentioning
confidence: 99%
“…Searching for bird species through scat, carcasses, or eggs has resulted in sensitivity rates between 62.6% and 100% with precision reported between 50% to 100% (Arnesen et al, 2020;Bolton et al, 2021;Fukuhara et al, 2022;Reynolds et al, 2021). However, the study by Arnesen et al (2020), where dogs searched for rock ptarmigan (Lagopus muta) scat in lab conditions, had three dogs out of four perform no better than chance and none of the dogs or handlers had any previous experience of training for CDD work.…”
Section: Effi C Ac Y R Ate S Across Conte X Tsmentioning
confidence: 99%
“…that contribute to the disruption of ecosystems and make them more favorable to outbreak occurrence ( Sandler et al, 1993 ; Rocke et al, 1999 ; Lafrancois et al, 2011 ). Knowing these factors can make possible the identification and the implementation of control management measures (in particular the collection and destruction of animal carcasses in areas at risk) ( Inger et al, 2016 ; Reynolds et al, 2021 ). Some studies demonstrated an interaction of environmental conditions (temperature, pH, sodium chloride and organic matter concentrations) affecting spore germination, outgrowth and toxin formation and proposed applied mathematical models ( Barras and Kadlec, 2000 ; Chea et al, 2000 ; Zhao et al, 2003 ).…”
Section: Clostridium Botulinum and Its Environmentmentioning
confidence: 99%
“…Litter should be protected from wild bird droppings. Wild birds can be asymptomatic carriers of C. botulinum, although the prevalence and conditions of this carriage is unknown ( Reed and Rocke, 1992 ; Reynolds et al, 2021 ).…”
Section: Botulism and Animalsmentioning
confidence: 99%
“…Serotypes A, B, E, and, occasionally, F give rise to botulism in humans, C and D are commonly associated with botulism of animals, and type G was usually isolated from soils ( Sonnabend et al, 1981 ; Woudstra et al, 2012 ; Kroumpouzos et al, 2021 ). BoNT/FA is a novel serotype discovered in 2016 with a hybrid-like structure of BoNT/A1 and BoNT/F5 ( Reynolds et al, 2021 ). As a 150 kDa protein containing a heavy chain (HC, 100 kDa) and a light chain (LC, 50 kDa) connected by a disulfide bond ( Lacy et al, 1998 ; Maslanka et al, 2016 ), BoNT has a zinc-dependent metalloprotease activity that cleaves SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins in peripheral neurons to block the release of neurotransmitters ( Swaminathan and Eswaramoorthy, 2000 ).…”
Section: Introductionmentioning
confidence: 99%